The role of regulation in influencing income-generating activities among public sector doctors in Peru - Jumpa Manuel; Jan Stephen; Mills Anne (BMC, 2007)
Abstract Objective To examine in Peru the nature of dual practice (doctors holding two jobs at once - usually public sector doctors with private practices), the factors that influence individuals' decisions to undertake dual practice, the conditions faced when doing so and the potential role of regulatory intervention in this area. Methods The study entailed qualitative interviews with a sample of twenty medical practitioners based in metropolitan Lima, representing a cross-section of those primarily employed in either the private or public sectors and engaged in clinical practice or policy making. The interviews focused on: 1. individuals' experience with dual practice; 2. the general underlying pressures that influence the nature and extent of such activities; and 3. attitudes toward, and the influence of, regulation on such activities. Results Dual practice is an activity that is widespread and well-accepted, and the prime personal motivation is financial. However, there are also a number of important broad macroeconomic influences on dual practice particularly the oversupply of medical services, the deregulated nature of this market, and the economic crisis throughout the country, which combine to create major hardships for those attempting to make a living through medical practice. There is some support among doctors for tighter regulation. Conclusion Research findings suggest appropriate policy responses to dual practice involve tighter controls on the supply of medical practitioners; alleviation of financial pressures brought by macro-economic conditions; and closer regulation of such activities to ensure some degree of collective action over quality and the maintenance of professional reputations. Further research into this issue in rural areas is needed to ascertain the geographical generalizability of these policy responses.